A descriptive study of mortality patterns amongst adult patients admitted to a tertiary care and teaching hospital - Dhar, Lovely; Mondal, Dipankar; Sarkar, Divit; Rana, Jigisha; Masanta, Madhushree; Sarkar, Manish; Maji, Debjyoti; Adhikary, Dibya; Das, Diya; Mondal, Kismotulla; Kayal, Mayukhe; Molla, Mazarul Rahaman; et al. (The ESRF Research Journal for Undergraduate Medical Students, 2024)
IntroductionData on mortality among hospitalised patients mostly reflect the aetiologies and distributions of severe illnesses as well ascommunity-level patterns of care-seeking. These hospital-based death records include details about the distribution ofdiseases and deaths by age and sex, among other things, that are extremely or critically important for organising healthcareservices. The present study was undertaken to classify deaths and describe the causes of death based on the age and sexof the patientsat the NRSMCH according to the International Classification of diseases (ICD-10).Materials and methodsThe present descriptive retrospective hospital-based study using records, was conducted at the Medical Records Department of NRSMCH between 1st January 2022 to 2nd March 2022, a total of 60 days. A complete enumeration of records of all849 deaths that occurred in NRSMCH during the study period was done. All data were recorded in predesigned pre-testedschedule, entered intoMicrosoft Excel (Microsoft Corp. USA) and analysed using SPSS, Version 20.ResultsThe mean age of patients in the study population was 54.9 (16.5) years with 36.2% females and 63.8% males.The commonest cause of death overall are diseases of the circulatory system (I00-I99) (39.8%) followed by injury and poisoning (S00-T98) (13.9%). Gender based analysis of deaths shows a higher proportion of deaths from diseases of the circulatory system(I00-I99) in both females (37.5%) and males (41.1%). The second most recorded cause of mortality was injury, poisoning(S00-T98) 13.9% overall and in both females (13%) and males (17.2%).Age group wise break-up of deaths show that thecommonest recorded cause of death in the 18- 40-year age group was injury, poisoning (S00-T98), followed by Certaininfectious parasitic diseases (A00 – B99) (18.1%). The commonest cause of death in the 41- 60-year age group wasDiseases of circulatory system (I00 – I99) (39.8%), followed by Injury, poisoning (S00 – T98) (11.7%). The commonestcause of death in the 61–80-year age group was Diseases of circulatory system (I00 – I99) (50.3%) while the second mostcommon was Injury, poisoning (S00 – T98) (9.9%). In patients over the age of 80 years the commonest cause of death isDiseases of circulatory system (I00 – I99) (56.4%) followed by Diseases of respiratory system (J00 –J99) (15.4%).ConclusionIn the present study, most common cause of overall mortality were diseases of the circulatory system (I00-I99) of which thecommonest was Nontraumatic intracerebral haemorrhage, Unspecified, I61.9. The single most common cause of death inthe study population was “Nontraumatic intracerebral haemorrhage, Unspecified”.No major differences were observed inthe proportion of males and females in terms of the causes of death. Age group wise break-up of deaths show that thecommonest recorded cause of death in the 18- 40 age group were “Injury, poisoning” (S00-T98), while the commonestcause of death in the 41-60, 61-80 and e” 81-year age group were “Diseases of circulatory system” (I00 – I99).